'Round midnight - Hancock, Herbie 1940- (The Criterion collection, 2022)
"’Round Midnight is a love letter from director Bertrand Tavernier to the heyday of bebop and the Black American musicians who found refuge in the smoky underground jazz clubs of 1950s Paris. In a sui generis, Oscar-nominated fusion of performer and character, legendary saxophonist Dexter Gordon plays Dale Turner, a brilliant New York jazz veteran whose music aches with beauty but whose personal life is ravaged by addiction. Searching for a fresh start in Paris, Turner strikes up an unlikely friendship with a struggling single father and ardent jazz fan (François Cluzet) who finds his life transformed as he attempts to help the self-destructive musician. Herbie Hancock’s evocative, Oscar-winning score sets the mood for this definitive jazz film, a bittersweet opus that glows with lived-in, soulful authenticity." [criterion.com]
Original: USA, Frankreich 1986
Blu-ray special edition features: new 4K digital restoration, with 2.0 surround DTS-HD Master Audio soundtrack ; alternate 5.1 surround soundtrack, presented in DTS-HD Master Audio ; new interview with jazz and cultural critic Gary Giddins ; new conversation with music producer Michael Cuscuna and author Maxine Gordon, widow of musician Dexter Gordon ; "Before midnight", a 1986 behind-the-scenes documentary by Jean Achache ; panel discussion from 2014 featuring Cuscuna, Maxine Gordon, director Bertrand Tavernier, and jazz scholar John Szwed, moderated by jazz critic and broadcaster Mark Ruffin ; performance from 1969 of "Fried bananas" by Dexter Gordon, directed by Teit Jørgensen ; new English subtitle translation and English subtitles for the deaf and hard of hearing ; plus: An essay by scholar Mark Anthony Neal
Bildformat 2.39:1
Keywords: Film; Blu-Ray-Disc